Asset Misappropriations Fraud: A Bibliometric Study - Setiawan, Nanang (E-Jurnal Akuntansi; Vol 34 No 2 (2024), 2024)
This research aims to carry out bibliometric analysis of 71 international journal articles on the topic of Asset Misappropriations (AM). This study is important considering that there is a lot of research on fraud but there is no AM mapping based on the type of fraud and fraud per industry. This bibliometric study uses NVIVO software with three analyses: word cloud, fraud classification, and fraud classification based on industry. The results of the analysis show that the dominant types of fraud in AM studied are theft of inventory, theft of cash and skimming. The dominant types of industry studied are banks, government sector, and retail. The dominant fraud in the banking industry is cash larceny; The dominant fraud in the government sector industry is theft of inventory; and the dominant fraud in the retail industry is theft of inventory. This study contributes to increasing literacy for academics about AM and becomes a recommendation for future research; also contribute to practitioners in creating anti-fraud policies for companies and other organizations. Keywords: Asset Misappropriation; Bibliometric Study; Fraud